Rental House System for UTHM Students - Yap, Kit Yeng; Hamzah, Mohd Hamdi Irwan (Applied Information Technology And Computer Science, 2024)
In Parit Raja, Johor, UTHM students who are not living in the university dormitory will need to rent houses around UTHM for academic purposes. The existing rental process is time-consuming since students need to go out off campus to find suitable houses and may face the problem of incomplete details of the house and the landlords. The objectives of this web-based platform are to design a rental house system using an object-oriented approach, to develop a rental house system using a web-based approach and to test the functionality and usability of the developed rental house system. This study used an iterative model of the software development life cycle to systematically design and develop the system. By comparing the system with existing systems, the system has unique features that set it apart from existing products. Ultimately, the system will enhance the housing search experience for UTHM students while providing administrative convenience for landlords and administrators. The Rental House System for UTHM Students successfully achieves the objectives and solves the problem facing by the stakeholders.